The Use of Gamification in Teaching Writing Skills to Junior High Students | IstikhdÄm Al Talâ€™Ä«b FÄ« Taâ€™lÄ«m MahÄrah Al KitÄbah Lada ThullÄb Al MadÄris Al Muthawassithah - Abdul Mutholib; Maâ€™rifatul Munjiah; Syamfa Agny Anggara (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
Writing as a language skill is still considered a language skill that is categorized as very difficult. Various kinds of problems arise in learning to write Arabic because writing skills are skills that combine various disciplines. Therefore, teachers must continually innovate in the learning process, such as choosing a learning model or using various learning methods, one of which is gamification-based Arabic learning. Gamification is a modern educational strategy popular in the West, namely educational stimulation by applying game elements and principles in non-game contexts. This article describes Gamification's use in teaching high school students writing skills. The research method used is the descriptive method with the desk research method. The results of the study show that the use of Gamification in teaching writing Alexistoto skills can improve the quality of learning, especially in Arabic, so that students can master writing skills in an easy and fun way, and can lead to the development of teaching writing skills in a social context following their interests, motivations, and needs Student. This study recommends further research to test the effectiveness of Gamification on other Arabic language skills with a more varied research method.